Promoting Social Dialogue in European Organizations: Human Resources Management and Constructive Conflict Management - Martin Euwema; Lourdes Munduate; Patricia Elgoibar; Erica Pender; Ana Belén García (Springer Open, 2015)
This volume focuses on describing the social dialogue system~in organizations~from an Human Resources Management perspective.~Based on the NEIRE model for industrial relations, key factors are determined~contributing to creative social dialogue in European organizations.~Actual data from surveys and interviews from more than 700~CEO and HR managers in eleven European countries~give insights in the experiences with and expectations of employers of social dialogue. The volume offers a comprehensive introduction to~the historical context~and~current situation~in social dialogue in these countries. This context helps to understand the current major challenges in each country when it comes to a vital social dialogue. Using good practices from many organizations, this book offers an agenda for innovative and cooperative social dialogue in organizations.
Keywords: 300; Industrial; Organisational and Economic Psychology; Social Policy; Political Science; general